Consumer Boycotts: Corporate Response and Responsibility - Hurrem Yilmaz; Abdullah Alhumoud (International Review of Management and Marketing, 2017)
Boycotts, once intended as short term signals to business to improve performance, are proving to have increasingly long term ramifications. Yet there is limited number of studies in consumer boycotts area and specifically on the effect of motivational factors. The current study investigates the effect of company response to crisis (appropriate vs. inappropriate) and company responsibility for the crisis (responsible vs. not responsible) on the perceived egregiousness of a company’s act, corporate image and boycott decision. Our study tests hypotheses and reports implications for marketing strategy and further research.